A simple and sensitive detection of small molecule–protein interactions based on terminal protection-mediated exponential strand displacement amplification. Issue 9 (10th April 2018) - Lee, Chang Yeol; Kim, Hyo Yong; Kim, Soeun; Park, Ki Soo; Park, Hyun Gyu
Abstract : A new strategy to detect a small molecule–protein interaction was devised based on terminal protection-mediated exponential strand displacement amplification (eSDA). Abstract : We herein describe a simple and sensitive strategy to detect a small molecule–protein interaction based on terminal protection-mediated exponential strand displacement amplification (eSDA). In principle, the small molecule linked to a DNA probe protects the DNA probe against the exonuclease I-catalyzed degradation after its binding to the corresponding target protein. The protected DNA probe then serves as a template to promote eSDA. Consequently, a large number of duplexes are produced, which leads to a high fluorescence from a double-stranded DNA specific fluorescent dye, SYBR Green I. As a model system to prove this sensing strategy, the interaction between biotin and streptavidin (SA), which is known to be the strongest among the non-covalent biological interactions, was selected and its analytical performance was thoroughly investigated. As a result, SA was sensitively detected with the limit of detection of 16 pM. In addition, the practical applicability of this method was successfully demonstrated by reliably determining the SA in human serum.